A model for ultimate bearing capacity of PVC-CFRP confined concrete column with reinforced concrete beam joint under axial compression. (30th July 2019) - Yu, Feng; Li, Dongang; Niu, Ditao; Zhu, Defeng; Kong, Zhengyi; Zhang, Nannan; Fang, Yuan
Highlights: Different failure modes for the PRJ and the PCRJ were found. The effects of several parameters on the ultimate bearing capacity were found. The PCRJ showed much better performance than that of the PRJ. A more accurate model for estimating the ultimate bearing capacity was suggested. Abstract: In this study, the experiment of one PVC confined concrete column with reinforced concrete beam joint (PRJ) and nine PVC-CFRP confined concrete columns with reinforced concrete beam joints (PCRJ) under axial compression were carried out. All specimens were designed based on the principle of strong joint and weak column. Different influencing parameters (i.e., the width, height, reinforcement ratio, and stirrup ratio of ring beam, and spacing of CFRP strips) were investigated. Two different failure modes for the PRJ and the PCRJ were found. The PRJ failed by the buckling of PVC tube while the PCRJ failed by the fracture of CFRP strips and cracking of PVC tube. The ultimate bearing capacity of the PCRJ decreased as the spacing of CFRP strips increased whiles the width, height, reinforcement ratio, and stirrup ratio of ring beam had no obvious influences on the ultimate bearing capacity. The PCRJ showed much better performance than that of the PRJ. Based on the design theory of the concrete filled steel tubular columns, a model for estimating the ultimate bearing capacity of the PCRJ subjected to axial compression was suggested, and it agreed well with test data.